EFFECTIVENESS OF BACTERIAL VAGINOSIS THERAPY IN PREGNANT WOMEN BY OCTENIDINE DIHYDROCHLORIDE ANTISEPTIC - O. N. Vasilchenko; O. R. Baev (Медицинский совет, 2016)
One of the first places in the structure of diseases of the female sexual organs is taken by bacterial vaginosis, which, by the literature data, is diagnosed in 30-57%  of women of the reproductive age [1, 2]. Bacterial vaginosis is an infectious noninflammatory syndrome characterized by a sharp reduction or lack of lactoflora and its replacement by polymicrobial associations of anaerobes and Gardnerella vaginalis, concentration of which achieves 109–1011 CFU/ml of vaginal discharge [3–5].